Combining ability and gene action for grain yield and associated traits in segregating generation of rice (Oryza sativa) - KUMAR, SANJEEV; SINGH, H B; SHARMA, J K; SOOD, SAILAJ (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2003 on 9 x 9 diallel mating design analysis in F, generation (excluding reciprocals) of rice (Ovza sativa L.) for grain yield, various yield components and some grain quality traits revealed significant differences for general and specific combining abilities for all the characters under studied. The magnitude of gca variance was relatively higher than sca variance and thus predominance of additive gene action (d) was observed for all the traits except for net-assimilation rate (g2), biological yield per plant (g), harvest index (%) and protein content (%). On the basis of gca effects, the parents ’HPR 2047’, ’VL 91-1754’ and ’JD 8’ were good general combiners for grain yield and most of its contributing characters. The crosses involving the any one of the above parents were more promising and therefore, these parents should be exploited in hybridization programmes. Based on highly significant specific combining ability (sca) effects, the cross combinations ’HPR 1164’ x ’HPR 2047’, ’HPR 1164’ x ’VLDhan 2211, ’China 988’ x ’VL 91-1754’ and ’HPR 2047’ x ’JD 8’ are suggested for isolation of hgh yielding lines through pedigree method.